Manajemen Stres Kerja Pengusaha Untuk Meningkatkan Kinerja Perusahaan Di Industri Batik Laweyan Surakarta - lukman hakim; Eko Sugiyanto (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2017)
This study aims to: (1) Identifying the causes of workplace stress occurring entrepreneurs in the batik industry Laweyan Surakarta Central Java. (2) Identify the effect or impact stress businessman working in the batik industry Laweyan Surakarta Central Java. (3) Develop a model of handling work stress entrepreneurs in the batik industry Laweyan Surakarta Central Java. This research uses descriptive method with a